SOCIAL VULNERABILITY AT SCHOOL - Silva, Flávia Francisca Ferreira da; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
School in modern times is characterized as a social environment in which most students spend most of their time, as it is a space understood as a privileged place for learning, not simply an irrefutable educational theme, as well as values and beliefs, which young people assimilate to confront themselves and live in society, in addition to developing critical sense, self-esteem and security (BYDLOWSKI; LEFÉVRE; PEREIRA, 2016, p. 47). Faced with such a scenario, it is proposed to investigate the conceptions of the school community in relation to failure in learning, thus seeking to understand how the social authors of the school community instigate mediators with social vulnerability in the constructive resource in the researched school, using various fields of knowledge such as pedagogical praxis (FERREIRA, 2020, p. 86), pedagogical resources (SOSA; MANZUOLI, 2019).